2007
DOI: 10.1016/j.ijid.2006.05.006
|View full text |Cite
|
Sign up to set email alerts
|

A population-based assessment of the disease burden of consolidated pneumonia in hospitalized children under five years of age

Abstract: Patients younger than two years of age predominated, being the main targets for anti-pneumococcal conjugated vaccines. Incidence rates provided evidence of the burden of consolidated pneumonia for childhood, estimating the potential benefits of vaccination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
1
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 17 publications
0
30
1
2
Order By: Relevance
“…Active surveillance studies have been taken place recently in Argentina, 37 Brazil, 38 and Uruguay. 39 The Region now has reliable and quality data regarding the S. pneumoniae capsular types, which have caused invasive disease in children less than 6 years old as well as information about their susceptibility to beta lactam antibiotics. 40 This information is of paramount importance to healthcare decision makers to enable them to prioritize public health interventions coupled with the post intervention surveillance data to evaluate their impact.…”
Section: Discussionmentioning
confidence: 99%
“…Active surveillance studies have been taken place recently in Argentina, 37 Brazil, 38 and Uruguay. 39 The Region now has reliable and quality data regarding the S. pneumoniae capsular types, which have caused invasive disease in children less than 6 years old as well as information about their susceptibility to beta lactam antibiotics. 40 This information is of paramount importance to healthcare decision makers to enable them to prioritize public health interventions coupled with the post intervention surveillance data to evaluate their impact.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported in LAC countries a sensitivity of blood culture to detect pneumococcal pneumonia of <10%. 36,54,69,70 The addition of non-culture methods, as polymerase chain reaction (PCR) testing, to routinely performed culture analysis may improve the estimated burden of disease. Arguedas reported, in a prospective epidemiologic surveillance study, an IPD incidence rate for culture positive only of 33.7/100,000 per year.…”
Section: Resultsmentioning
confidence: 99%
“…The studies conducted in Uruguay, Brazil and Argentina demonstrated similar results in terms of CP incidence. 3,[14][15][16] Data from Pilar were used as baseline in this study to measure the importance of the intervention in the post-vaccine period.…”
mentioning
confidence: 99%
“…19 Studies found in the international and Latin American bibliography have also demonstrated the role of influenza virus in the etiology of these clinical forms. 14,20,21 Further investigations are required on cases of viral and bacterial co-infection.…”
mentioning
confidence: 99%